Pengaruh Clinical Pathway Terhadap Mutu Pelayanan Keperawatan dan Kepuasan Pasien - lenny widjaja; Catharina Dwiana Wijayanti; Emiliana Tjitra (UIMA Press, 2019)
ABSTRACT At X Hospital, 6 Clinical Pathways (CPs), 4 medical surgeries and 2 infectious diseases have been performed by nurse since 2014. To improve the quality of nursing services and patient satisfaction, a study was conducted on the effect of increasing the application of CP. The design of this study was a quasi experimental pre-post test and with a control group. The study group was determined based on the distribution of 6 CP cases and the type of inpatient services (private and government insurance). The study was conducted for 8 weeks in 4 nursing wards. During the first 4-week and after the intervention CP documents were auditted, analyzed the quality of nursing services and patient the standard X hospital forms. CP refreshing was given to 35 nurses of the intervention group selected satisfaction using by purposive sampling technique from 2 predetermined nursing wards The characteristics of nurses between the study groups did not differ, except more proportion of male nurses in the intervention than in control groups (22,9% vs 3,0%) Characteristics of inpatients, at before and after the intervention between the study groups were varied in age , and admitted diagnosis. The application of CP at pre-test was incomplete in both study groups, and after CP refreshing there was an improvement implementation of CP only in the intervention group (0 vs 68,6%). The quality of nursing services also improved only in the intervention group (62,9% vs 97,1%). Patient satisfaction had not significantly improved in both study group, either at pre or post tests.Overall, characteristics of nurse and patient and refreshing of CP did not affect the implementation of CP, quality of nursing services and patient satisfaction. While the of CP affected patient satisfaction, and the quality of nursing services affected the patient satisfaction. In conclusion, increasing the implementation of CP can improve the quality of nursing services and patient satisfaction. Keywords: Clinical Pathway, quality of nursing services, patient satisfaction